Clinical effectiveness of the massachusetts childhood obesity research demonstration initiative among low‐income children. Issue 7 (July 2017) - Taveras, Elsie M.; Perkins, Meghan; Anand, Shikha; Woo Baidal, Jennifer A.; Nelson, Candace C.; Kamdar, Neil; Kwass, Jo‐Ann; Gortmaker, Steven L.; Barrett, Jessica L.; Davison, Kirsten K.; Land, Thomas
Abstract : Objective: To examine the extent to which a clinical intervention resulted in reduced BMI z scores among 2‐ to 12‐year‐old children compared to routine practice (treatment as usual [TAU]). Methods: The Massachusetts Childhood Obesity Research Demonstration (MA‐CORD) project is a multifaceted initiative to prevent childhood obesity among low‐income children. At the federally qualified community health centers (FQHCs) of two communities (Intervention Site #1 and #2), the following were implemented: (1) pediatric weight management training, (2) electronic decision supports for clinicians, (3) on‐site Healthy Weight Clinics, (4) community health worker integration, and (5) healthful clinical environment changes. One FQHC in a demographically matched community served as the TAU site. Using electronic health records, we assessed BMI z scores and used linear mixed models to examine BMI z score change over 2 years in each intervention site compared to a TAU site. Results: Compared to children in the TAU site ( n = 2, 286), children in Intervention Site #2 ( n = 1, 368) had a significant decline in BMI z scores following the start of the intervention ( − 0.16 units/y; 95% confidence interval: − 0.21 to − 0.12). No evidence of an effect was found in Intervention Site #1 ( n = 111). Conclusions: The MA‐CORD clinical interventions were associated with modest improvement in BMI z scores in one of two intervention communities compared to a TAU community.